The Implementation of Christian Religious Education and Its Contribution to the Spirituality of Generation Z Adolescents: A Descriptive Study at GMIBM Paulus Pusian - Devis Oktavianus Pinontoan; Fernando Turangan; Steviani Koikig; Rani Jacobus; Befri Guma (Jurnal Ilmu Pendidikan dan Sosial, 2025)
This study aims to describe the implementation of Christian Religious Education (CRE) and its impact on the spirituality of Generation Z adolescents at the Evangelical Christian Church in Bolaang Mongondow (GMIBM) Paulus Pusian. The research problem departs from the challenges Generation Z faces in the digital era, such as the rapid growth of information technology, social media, and shifting social values that may affect adolescent spiritual life, so that CRE becomes an essential means for the church to nurture faith, character, and the spirituality of the young generation. The method employed was qualitative descriptive, with data gathered through participatory observation, in-depth interviews, and documentation of youth ministry at GMIBM Paulus Pusian. Data were analyzed through the stages of data reduction, data display, and conclusion drawing to obtain a comprehensive picture of CRE implementation and its impact on adolescent spiritual life. The findings show that CRE at GMIBM Paulus Pusian is implemented through various nurturing activities such as youth worship, Bible study, prayer fellowship, spiritual mentoring, and involvement in church ministry. It is concluded that CRE implementation contributes positively to the spiritual growth of Generation Z adolescents; therefore, the church needs to develop a contextual, relevant, and adaptive nurturing model to sustainably support the faith and spiritual formation of the young generation.